Targeted therapy in advanced metastatic colorectal cancer: Current concepts and perspectives - Hohla, Florian (Baishideng Publishing Group Inc, 2014)
The introduction of new cytotoxic substances as well as agents that target vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) signaling has improved clinical outcome of patients with metastatic colorectal cancer (mCRC). In this review we summarize the most relevant clinical data on VEGF and EGFR targeting regimens in mCRC. The effects of available treatment strategies for mCRC are often temporary, with resistance and disease progression developing in most patients. Thus, new treatment strategies are urgently needed. Some GI peptides including gastrin and gastrin releasing peptide, certain growth factors such as insulin-like growth factor-I and II and neuropeptides such as growth hormone releasing hormone (GHRH) are implicated in the growth of CRC. Experimental investigations in CRC with antagonistic analogs of bombesin/gastrin-releasing peptide, GHRH, and with cytotoxic peptides that can be targeted to peptide receptors on tumors, are summarized in the second part of the review.